Characterizing the Use of Telepsychiatry for Patients with Opioid Use Disorder and Cooccurring Mental Health Disorders in Ontario, Canada. (11th February 2018) - LaBelle, Brittanie; Franklyn, Alexandra M.; PKH Nguyen, Vicky; Anderson, Kathleen E.; Eibl, Joseph K.; Marsh, David C.
Abstract : Rural patients with opioid use disorder (OUD) face a variety of barriers when accessing opioid agonist therapy (OAT) and psychiatric services, due to the limited supply of physicians and the vast geographic area. The telemedicine allows for contact between patients and their physician—regardless of physical distance. Objective . We characterize the usage of telemedicine to deliver psychiatric services to patients with OUD in Ontario, as well as traits of treatment-seeking patients with opioid dependence and concurrent psychiatric disorders. Methodology . A retrospective cohort study was conducted using an administrative database for patients who received psychiatric services via telemedicine between 2008 and 2014 and who also had OUD. Results. We identified 9, 077 patients with concurrent opioid use and other mental health disorders who had received psychiatric services via telemedicine from 2008 to 2014; 7, 109 (78.3%) patients lived in Southern Ontario and 1, 968 (21.7%) in Northern Ontario. Telemedicine was used more frequently to provide mental health services to patients residing in Northern Ontario than Southern Ontario. Conclusion . Telemedicine is increasingly being utilized throughout Ontario for delivering mental health treatment. There is an opportunity to increase access to psychiatric services for patients with opioid dependence and concurrent psychiatric disorders through the use of the telemedicine.